The Copyright Book - William S. Strong (The MIT Press, 2014)
At their best, our laws embody our deepest assumptions about human beings and what proper relations among human beings ought to be. Copyright is such a law. It springs from the belief that those who try to contribute to our always inadequate store of information and inspiration ought to be paid for their pains. This seems a very creditable attitude. My purpose in writing this book has been to make available to people whose lives and work are affected by the laws of copyright an understanding of their rights and responsibilities. However, I hope that in doing so I have also managed to communicate some of my own fascination with the subject. I have found it useful to write much of this book as though from the standpoint of the creator of a work— be it a novel, a painting, a blueprint, a dance. But whatever is not kept safe for the artist is given to the public; if you are a would-be user of an artistic or other creative work, you will know your boundaries by the boundaries drawn for the creator of it. I have tried to gather material and organize it in a way that will tell the story simply. This has not proved possible in all respects; parts of the law are so complex that no amount of pruning and rearranging could make them any less dense. Nor has it proved possible at every point to avoid technical language and terms whose legal definition differs from their ordinary meaning. In such places I have given examples to try to make clear what is being said